Takotsubo stress cardiomyopathy, a great mimicker of myocardial infarction in post-operative period: what surgeons should know? a case series - ., Soundappan; ., Swaminathan; Vijai, Anand; Kumar, Prashanth Ashok; John, Joseph; Harsha, Muvva Sri; Gajdhar, Aniq Ur Rehman (International Surgery Journal, 2022)
Takotsubo stress cardiomyopathy (TCM) is a rare disorder of the myocardium precipitated mainly by physical, mental stress or sometimes due to non-specific factors. The clinical presentation of takotsubo cardiomyopathy is an eidetic image of CAD and myocardial infarction (MI), but unlike the later takotsubo cardiomyopathy in most cases is reversible. Coronary angiographic evidence showing the absence of narrowing of coronary vessels is the only definitive way to distinguish this from MI. This condition is a less familiar entity to the surgeons and knowing this will help in arriving at the diagnosis early and have an optimistic attitude towards management because the condition is a self-limiting and good recovery is seen generally with supportive management. In this series, 1056 HPB cases and 101 liver transplant cases done from January 2016 to February 2021 and among them we describe four cases who developed TCM in post-operative period and discuss the relevant literature.